A Beginner’s Guide to Water Management — Bacteria - Florida LAKEWATCH (EDIS)
This 44-page booklet starts with a brief tutorial on the presence of bacteria in Florida lakes, and the aquatic environment in general, and then quickly turns to the subject that lake users are most interested in: possible sources of bacterial contamination and how to test for it. The discussion includes a comparison of the effectiveness of wastewater treatment plants versus septic tanks. Also, indicators used for detecting bacterial contamination are explained, along with basic laboratory methods. Lastly, an easy 4-step process is provided for tracking down bacterial contamination in a waterbody. Laboratory suppliers are listed at the end for individuals or groups interested in doing their own bacterial sampling. This document, CIR106, is the sixth of a series of information circulars dedicated to familiarizing citizens with the language and techniques used by those involved in water management. February 2003 © 1st Edition.